Selenium as a Bioactive Micronutrient in the Human Diet and Its Cancer Chemopreventive Activity - Radomska, Dominika (Nutrients, 2021)
This review answers the question of why selenium is such an important trace element in the human diet. Daily dietary intake of selenium and its content in various food products is discussed in this paper, as well as the effects of its deficiency and excess in the body. Moreover, the biological activity of selenium, which it performs mainly through selenoproteins, is discussed. These specific proteins are responsible for thyroid hormone management, fertility, the aging process, and immunity, but their key role is to maintain a redox balance in cells. Furthermore, taking into account world news and the current SARS-CoV-2 virus pandemic, the impact of selenium on the course of COVID-19 is also discussed. Another worldwide problem is the number of new cancer cases and cancer-related mortality. Thus, the last part of the article discusses the impact of selenium on cancer risk based on clinical trials (including NPC and SELECT), systematic reviews, and meta-analyses. Additionally, this review discusses the possible mechanisms of selenium action that prevent cancer development.